1987
DOI: 10.1002/path.1711530312
|View full text |Cite
|
Sign up to set email alerts
|

Nucleolar organizer regions in small cell tumours of childhood

Abstract: A silver colloid technique for nucleolar organizer regions (AgNORs) was applied to paraffin sections of 50 small cell tumours of childhood. These comprised 20 neuroblastomas, 10 Ewing's sarcoma, and 20 rhabdomyosarcomas, including spindle cell, myxoid, and round cell variants. On the basis of the number of AgNORs, one could differentiate between the three groups. The differences observed were statistically significant (P = 0.01-0.001). The subtypes of rhabdomyosarcoma could not be distinguished from one anothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0
1

Year Published

1992
1992
2006
2006

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(11 citation statements)
references
References 19 publications
0
10
0
1
Order By: Relevance
“…One study by Egan et al 1987 studied AgNOR counts in 20 RMS, 20 neuroblastoma, and 10 Ewings sarcoma and found that mean AgNOR counts tended to be characteristic of each particular histology with RMS having the least counts followed by Ewings Sarcoma and neuroblastoma the most. A study of 194 adult soft tissue sarcomas revealed that AgNOR count was an independent prognostic factor in a multivariate analysis with mitotic count, extent of necrosis, cellularity, cellular pleomorphism, extent of myxoid change, sclerosis, nonspecific histological diagnosis, and mast cell counts (Tomita et al, 1993).…”
Section: Discussionmentioning
confidence: 96%
“…One study by Egan et al 1987 studied AgNOR counts in 20 RMS, 20 neuroblastoma, and 10 Ewings sarcoma and found that mean AgNOR counts tended to be characteristic of each particular histology with RMS having the least counts followed by Ewings Sarcoma and neuroblastoma the most. A study of 194 adult soft tissue sarcomas revealed that AgNOR count was an independent prognostic factor in a multivariate analysis with mitotic count, extent of necrosis, cellularity, cellular pleomorphism, extent of myxoid change, sclerosis, nonspecific histological diagnosis, and mast cell counts (Tomita et al, 1993).…”
Section: Discussionmentioning
confidence: 96%
“…Fibrosarcoma can be differentiated from fibrous proliferations (Egan et al, 1988a) and neuroblastoma can be differentiated from other small round cell tumours on the basis of AgNOR counts (Egan et al, 1987). AgNOR numbers are strongly correlated with histopathological prognostic indices of neuroblastoma and are an independent prognostic indicator in that condition (Egan et al, 1988b).…”
Section: Endocrine Tumoursmentioning
confidence: 99%
“…[10][11][12][13] AgNOR analysis has been shown to be useful for diagnosis of malignant tumors of different cell types. 14,[15][16][17][18] To date only two studies have demonstrated the positive diagnostic value of AgNOR analysis in nasopharyngeal carcinoma (NPC). Their conclusions were based on optical counting of the AgNOR numbers.…”
mentioning
confidence: 99%